Synthesis and characterization of semirefined carrageenan/glycerol packaging film incorporated with tannic acid and different concentration of titanium dioxide - Khadijah Husna, Abd Hamid; Jayakumar, Tarchiani; Nurul Aini, Mohd Azman (AIP Publishing, 2025)
Plastic packaging generates a significant amount of waste due to its poor biodegradability, recyclability, and biocompatibility. An environmentally conscious approach to addressing this issue involves creating biopolymers by incorporating natural plasticizers, antioxidants, and nanoparticles into a film. This study designed a film composed of semirefined carrageenan (SRC), natural glycerol (G), tannic acid (TA), and varying quantities of titanium dioxide (TiO2). The film's characterization was evaluated through mechanical and physical properties, and the functional group of the film was observed by Fourier-transform infrared spectroscopy (FTIR). The physical properties of the film exhibited enhancement with the ascending concentration of TiO2, ranging from 1% to 9% (w/v). When 0.08% w/v TA and 3% w/v TiO2 were added to the SRC film samples, they exhibited a significantly favorable tensile strength of 27.80 MPa and an elongation at break of 14.35 %. Thus, the formulation of TA-enriched SRC and contains different concentrations of TiO2, has the potential to maintain the integrity of packaged food and offers a viable alternative for active packaging.